Estudio de factibilidad para la creación de un centro de acopio y comercialización de papa en la parroquia Toacazo. - Gualpa Chuqui, Edison Marcelo (2019)
The present project aims to know the feasibility, for the creation of the potato collection center in the Parish of Toacazo in order to market the product at a fair price for farmers, small farmers in the communities of the upper zone will benefit the parish, reducing the chain of intermediaries thus avoiding payment at a lower price than the market. The study begins with the market research carried out by means of a survey of producers in the same area, where 92% of acceptability was obtained for the creation of the Collection Center and the willingness of the farmers to deliver this product from the center, in the same way the restaurants and supermarkets of Latacunga canton are willing to buy the product. A location analysis was carried out, which will be located in a strategic place close to all the communities in the upper area of the Parish since it has the largest number of farmers who are dedicated to the cultivation of potatoes and also has factors that favor the development of the project. In the organizational study we find the structural organization chart of the microenterprise and the functions that the staff must fulfill. For the creation of the collection center, an investment of $ 66,828.38 is required, the same dollars that Banecuador will finance with 60% of the investment and the partners will contribute 40% of their own capital. The study of the project indicates to be feasible in the technical stage in the financial evaluation, through the indicators VAN $ 4.832,68, internal rate of return 16% and the ratio benefited 1.05. During the operational life of the Collection Center generating more 7 direct jobs and more than 200 families indirectly. Finally, it performed an impact analysis in the economic, business, environmental aspects with their respective indicators, which resulted in a high positive overall impact.